On the problem of shear of a functionally graded half-space by a punch - Zelentsov Vladimir (MATEC Web of Conferences, 2017)
Contact problem on shear of a functionally graded half-space by a strip bunch was considered. Shear modulus of the half-space is exponentially increasing by depth. The contact problem was reduced to a convolution integral equation of the first kind. Solution of the integral equation was constructed by asymptotic methods over the characteristic parameter of the problem. Dependence of the obtained problem solution and its main characteristics on the shear modulus of the half-space was analysed. Expressions for the main characteristics of the problem are given.